Aberrant lipid metabolism in cancer cells – the role of oncolipid‐activated signaling. (23rd October 2017) - Ray, Upasana; Roy, Sib Sankar
Abstract : Metabolic activity of malignant cells is very different from that of their nontransformed equivalents, which establishes metabolic reprogramming as an important hallmark of every transformed cell. In particular, the current arena of research in this field aims to understand the regulatory effect of oncogenic signaling on metabolic rewiring in transformed cells in order to exploit this for therapeutic benefit. Alterations in lipid metabolism are one of the main aspects of metabolic rewiring of transformed cells. Up‐regulation of several lipogenic enzymes has been reported to be a characteristic of various cancer types. Lysophosphatidic acid (LPA), a simple byproduct of the lipid biosynthesis pathway, has gained immense importance due to its elevated level in several cancers and associated growth‐promoting activity. Importantly, a current study revealed its role in increased de novo lipid synthesis through up‐regulation of sterol regulatory element‐binding protein 1, a master regulator of lipid metabolism. This review summarizes the recent insights in the field of oncolipid LPA‐mediated signaling in regard to lipid metabolism in cancers. Future work in this domain is required to understand the up‐regulation of the de novo synthesis pathway and the role of its end products in malignant cells. This will open a new arena of research toward the development of specific metabolic inhibitors that can add to the pre‐existing chemotherapeutics in order to increase the efficacy of clinical output in cancer patients. Abstract : Combinatorial targeting of the de novo lipid synthesis pathway and autotaxin–lysophosphatidic acid signaling axis attenuates the proliferation of transformed cells depending on the distinct cancer type. This eventually results in the arrest of tumor progression and is thus a promising strategy for the improved efficacy of existing therapeutic interventions.